PENGGUNAAN ABU TERBANG BATUBARA PADA PEMBUATAN BATAKO DI KOTA PALU - Mashuri, Mashuri; Adam, Andi Arham; Rahman, Rahmatang; Setiawan, Arief (MEKTEK, 2012)
One cause of the poor quality of some concrete blocks in the city of Palu is the lack of cement used in the concrete block. This is caused by the high price of cement so that income of concrete blocks maker decreases. To find a way out of these problems, a lot of waste material that can be used in the manufacture of concrete block, one of which is coal fly ash. The purpose of this activity is to introduce the use of coal fly ash in the manufacture of concrete block to business partners of the concrete block makers in Palu city. The purpose of this activity is to make concrete block business group partners can increase their income without compromising quality concrete block produced.Activity counseling / coaching and mentoring manufacturing concrete block using coal fly ash has been done to the concrete block makers. To facilitate the implementation of the concrete block-making, each made the graduated graduated barrel of sand, cement and coal fly ash graduated. To facilitate the implementation of the concrete block-making, made barrel graduated ie graduated sand, cement and coal fly ash graduated. The composition of the mixture is introduced to the partners is 0.75 sacks of cement: 0.25 sacks of coal fly ash and ± 300 kg of sand or 1 cement barrel dose: 1 coal fly ash barrel dose and 2 sand barrels doses. The results of this activity is to get that quality of concrete blocks produced by using coal fly ash strongly increased compressive strength but does not increase the quality of concrete blocks (Remain quality II). This activity was also found that any use of the three sacks of cement will result in an additional gain of ± 130 concrete blocks. This indicates that the use of coal fly ash in the manufacture of concrete blocks to provide added value to the concrete blocks makers.